The Impact of Girl-Child School Dropout on The Economic Development in Nyamirima Sub-County Kanungu District. - Tumukurate, Innocent (Kabale University, 2024)
The purpose of the study was to investigate the impact of girl school dropout on the economic development in Nyamirama sub-county Kanungu district. The study objectives were; To examine the impact of girl-child school dropouts on economic development, To find out the causes of girl-child school dropouts at the primary school level, and To come up with solutions to promote girl-child education in primary schools. the study was conducted in five randomly selected primary schools in Nyamirama Sub-county Kanungu district. A total sample of 157 respondents out of 291 targeted Populations were selected to participate in the study. Sampled respondents were pupils (65) teachers, (22) Head teachers, (05), and parents (65). The researcher used questionnaires and interviews as research tools in collecting the necessary data about the subject. The collected data was analyzed using both qualitative and quantitative techniques and presented in tables, frequencies, and percentages. The findings of the study revealed that there were impacts of girl-child school dropouts on economic development, causes of girl-child school dropout in primary schools, and possible solutions to promote girl-child education in primary schools. the researcher recommended that girls should not be harassed both within and outside schools. there should be a conducive learning environment. Domestic chores should be reduced per girl child during school hours. The community should participate in school activities both academic and non-academic activities. There should be a delay of early marriages for girls. There should be good upbringing of children from home. Areas for further study will be about the effect of early marriages on girl child in primary schools.